Pengembangan Pop-up Book Digital untuk Meningkatkan Pemahaman Konsep Kelas IV Materi Bagian Tumbuhan dan Fungsinya - Aida Susilawati; Atep Sujana; Enjang Yusup Ali (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research is based on the problem, namely the minimal use of media in learning, so that it seems monotonous which has an unfavorable impact on learning activities, resulting in student learning outcomes on average not being optimal because conceptual understanding of the material is still low, so research and development is carried out with the aim of knowing media design, knowing the suitability of media, and knowing how to increase understanding of class IV concepts by using media with the R&D method and the 6 stages in the ASSURE model. The research carried out resulted in media suitability from media experts giving a score of 94.6%, material experts 92%, and learning experts 81.3%, resulting in an average expert validation result of 89.3%, including the very feasible category. Media trials in small groups resulted in a value of 84.2% and in large groups 84.3%. Digital pop-up book media has a positive influence on learning, there is an increase in students' understanding of concepts which can be seen in the average pre-test score and based on the N-Gain test there is an increase of 0.60, including an increase in the moderate category.